Contesting performance : global sites of research - McKenzie, Jon; Roms, Heike; Wee, C. J. Wan-ling (Basingstoke, Hampshire : Palgrave Macmillan, 2012)
"Contesting Performance is a unique and dynamic collection of essays by leading international scholars that addresses the global development of cultural performance research. The volume functions as a critical reader on diverse, localised approaches to studying performance, using case studies from Mexico, Australia, Japan, Israel and Croatia, amongst others. Featuring contributors such as Freddie Rokem, Shannon Jackson, Lauren Kruger and Sharon Aronson-Lehavi, this landmark collection will also reveal networks of practical and theoretical concerns that contest dominant models of performance studies"--Provided by publisher.
Introduction : contesting performance in an age of globalization / Jon McKenzie, C.J. W.-L. Wee, and Heike Roms -- The many lives of performance : the Hemispheric Institute of Performance and Politics / Diana Taylor -- Interdisciplinary field or emerging discipline? : performance studies at the University of Sydney / Gay McAuley -- The practice turn : performance and the British Academy / Heike Roms -- Rhetoric in ruins : performance studies, speech, and the 'Americanization' of the American University / Shannon Jackson -- Performance studies in Japan / Uchino Tadashi and Takahashi Yuichiro -- Between antipodality and relational performance : performance studies in Australia / Edward Scheer and Peter Eckersall -- Critical writing and performance studies : the case of the Slovenian journal Maska / Bojana Kunst -- 'Say as I do' : performance research in Singapore / Ray Langenbach and Paul Rae -- The performance of performance research : a report from Germany / Sybylle Peters -- Translate, or else : marking the glocal troubles of performance research in Croatia / Lada Čale Feldman and Marin Blažević -- Performing postcoloniality in the Moroccan scene : emerging sites of hybridity / Khalid Amine -- Searching for the contemporary in the traditional : contemporary Indonesian dance in Southeast Asia / Sal Murgiyanto -- Word and action in Israeli performance / Sharon Aronson-Lehavi and Freddie Rokem -- Democratic actors and post-apartheid drama : contesting performance in contemporary South Africa/ Loren Kruger.
Bibliografija uz poglavlja. - Kazalo
Keywords: Performance -- Evaluation; izvedba -- evaluacija; kazalište; izvedbene umjetnosti